2018
DOI: 10.1155/2018/6529283
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Peritoneal Dialysis Treatment in Patients with Refractory Congestive Heart Failure due to Chronic Cardiorenal Syndrome

Abstract: Aims To evaluate the effectiveness and safety of peritoneal dialysis (PD) in treating refractory congestive heart failure (RCHF) with cardiorenal syndrome (CRS). Methods A total of 36 patients with RCHF were divided into type 2 CRS group (group A) and non-type 2 CRS group (group B) according to the patients' clinical presentations and the ratio of serum urea to creatinine and urinary analyses in this prospective study. All patients were followed up till death or discontinuation of PD. Data were collected for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
3
12
0
1
Order By: Relevance
“…There was a significant decrease in patients’ body weight in our study. This result was consistent with previous studies [22, 23]. We found a significant reduction in the degree of ascites, pretibial edema, and pleural effusion.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…There was a significant decrease in patients’ body weight in our study. This result was consistent with previous studies [22, 23]. We found a significant reduction in the degree of ascites, pretibial edema, and pleural effusion.…”
Section: Discussionsupporting
confidence: 94%
“…In a meta-analysis [13] ( n = 282) of six studies, in which ESRD patients were not included, no significant change in eGFR after PD treatment was reported. In the study by Shao et al [22], there was no significant change in eGFR of patients with type 2 CRS after PD, but the decrease in eGFR in patients with other types of CRS was significant. The reason for this increase of eGFR in the first three months may be related to decreased intra-abdominal pressure and improvement of renal perfusion.…”
Section: Discussionmentioning
confidence: 97%
“…Diálise peritoneal, outra modalidade de terapia renal substitutiva, está relacionada com uma estabilidade hemodinâmica em pacientes com insuficiência cardíaca. Dentre seus benefícios destacam-se um alívio nas pressões intraabdominais e na pressão venosa renal, além de poder drenar ascites, melhorar a taxa de filtração glomerular, aumentar a diurese e normalizar a creatinina sérica (Shao et al, 2018;Grossekettler et al, 2019).…”
Section: Discussionunclassified
“…14-17 In addition, recent reviews have demonstrated that PD is a safe and feasible treatment for the management of symptoms in patients with refractory HF. 18,19…”
Section: Discussionmentioning
confidence: 99%